2021
DOI: 10.1371/journal.pone.0256611
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesic effects of paravertebral block versus erector spinae plane block for thoracic and breast surgery: A meta-analysis

Abstract: Background Paravertebral block (PVB) is the most recognized regional anesthesia technique after thoracic epidural anesthesia for postoperative analgesia in thoracic and breast surgery. Erector spinae plane block (ESPB) is a recently discovered blocking technique, and it has evidenced excellent postoperative analgesia for breast and thoracic surgery with fewer adverse reactions. However, there are controversies about the postoperative analgesic effects of the two analgesic techniques. Objective To assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
0
18
2
2
Order By: Relevance
“…Moreover, contra-indications to thoracic epidural analgesia do not preclude PVBs in most cases. For thoracic surgeries, such as thoracotomies, PVBs provide better postoperative analgesia and lower opioid consumption than ESP blocks and RLBs [26][27][28]. Although conflicting results have been reported for breast cancer surgery [29], the analgesic efficacy of PVBs was found to be superior to that of ESP and other truncal blocks [7].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Moreover, contra-indications to thoracic epidural analgesia do not preclude PVBs in most cases. For thoracic surgeries, such as thoracotomies, PVBs provide better postoperative analgesia and lower opioid consumption than ESP blocks and RLBs [26][27][28]. Although conflicting results have been reported for breast cancer surgery [29], the analgesic efficacy of PVBs was found to be superior to that of ESP and other truncal blocks [7].…”
Section: Clinical Evidencementioning
confidence: 99%
“…Of interest, there are some reports suggesting the efficacy of ESPB in preventing acute PSP in this indication; some of them are randomized. In three meta-analyses, researchers compared the effect of ESPB to that of TPVB, but 2 also included thoracic surgery patients [25,27]. One meta-analysis included patients undergoing total mastectomies and found no statistically significant difference in morphine consumption at 24 hours [24].…”
Section: Plos Onementioning
confidence: 99%
“…However, there is no large study comparing ESPB to TPVB for major breast surgery. The available studies comparing ESPB to TPVB have shown analyses of a relatively low number of patients, and their results are pooled in several meta-analyses that have shown conflicting results [24][25][26][27]. Thus, the role of ESPB in the strategy of analgesia for breast surgery is not clearly defined, and the comparison of ESPB performance with that of TPVB will provide some answers.…”
Section: Introductionmentioning
confidence: 99%
“…Geleneksel olarak TPVB'nin meme cerrahilerinde postoperatif akut ağrı kontrolünde etkinliği kabul edilmiştir (6,7). Buna rağmen daha deneyimli klinisyenler tarafından yapılması önerilir (8). Son yıllarda Erector Spina Plan Bloğu (ESPB) güvenli ve etkin bir yöntem olarak gündeme gelmiştir (9).…”
Section: Introductionunclassified
“…%6.41 bulunmuştur(19). Çalışmamızda POBK oranlarına bakıldığında TPVB ve ESPB yapılan hastalarda, yapılan metaanaliz ve çalışmalarla uyumlu olarak fark bulunmadı(8,12,21). Bu sonuç gruplar arasında klinik olarak anlamlı olmayan morfin tüketim miktarlarına bağlanabilir.…”
unclassified